Analisis Korelasi Nilai Entrance Surface Air Kerma (ESAK) Terhadap Massa Tubuh, Usia, dan Faktor Eksposi pada Pasien Pemeriksaan Radiografi Umum di RSUP Dr. M. Djamil Padang - Putri, Rahmiatul; Milvita, Dian; Pratama, Ida Bagus Gede Putra (Jurnal Fisika Unand, 2025)
Research on the correlation analysis of Entrance Surface Air Kerma (ESAK) values ​​on body mass, age and exposure factors in general radiography examination patients was carried out at RSUP Dr. M. Djamil Padang. Data collection was carried out on adult patients with body mass (50-70) kg and age over 15 years on examination of the abdomen, thorax and lumbar spine for 3 months with a total of 1,113 patients. The method used to determine correlation is simple linear correlation test analysis. The results of the study showed that the ESAK value had a fairly strong correlation with the patient's body mass with an rxy value = 0.25-0.4 except for the lumbar spine examination. The ESAK value has a fairly strong to strong correlation with the exposure factor (kV) with a value of rxy = 0.27-0.6 and has a strong to very strong correlation with the exposure factor (mAs) as indicated with a value of rxy = 0.45 -0.9, but has a very weak correlation with patient age with a value of rxy = 0.02-0.1 except for lateral thorax examination.